Electrochemical immunosensor for detection of CA 15-3 biomarker in point-of-care - Rebelo, Tânia (2021)
This work reports the development of a simple and rapid electrochemical immunosensor for the determination of breast cancer biomarker Cancer Antigen 153 (CA153). Disposable and cost-effective chips, consisting of gold screen-printed electrodes (AuSPEs), were used to develop the portable electrochemical devices for monitoring the biomarker in point-of-care (PoC), under clinical context. The biosensor preparation consisted of two simple steps. First, a self-assembled monolayer (SAM) of mercaptosuccinic acid (MSA) was formed at the AuSPE surface. Then, the CA153 antibody was covalently bound to the carboxylic groups standing at the electrode surface using EDC/NHS chemistry. The performance of the developed immunosensor was evaluated by assessing the sensor sensitivity, linear response interval, selectivity and detection limit (LOD). The developed immunosensor provided a wide linear concentration range (from 1.0 to 1000UmL1) and low detection levels were achieved (LOD of 0.95UmL1), enabling the sensitive detection of the cancer biomarker at clinically relevant levels, using square wave voltammetry (SWV) as electroanalytical technique. Moreover, selectivity studies performed against other cancer biomarkers (CA 125 and CA 199) revealed that the antibody has high selectivity for CA15-3 antigen. The immunosensor was applied to the quantification of CA15-3 in artificial serum samples with satisfactory results.